2009
DOI: 10.1080/09670870802601084
|View full text |Cite
|
Sign up to set email alerts
|

Simulation studies of Senegalese Grasshopper ecosystem interactions I: the ecosystem model

Abstract: I present a model that could simulate the ecosystem dynamics of the Senegalese Grasshopper (Oedaleus senegalensis, Krauss) in the Sahel. It included the migration of the grasshopper by simulating the population dynamics and migration in a number of locations along a south-north transect. The model ecosystem in each location comprised: (i) millet, (ii) a natural Sahelian grass representing the grassland vegetation, (iii) the Senegalese grasshopper; (iv) a less important grasshopper, Acrotylus blondlii, Saussure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…This 'bet hedging' strategy developed by the Senegalese grasshopper does not seem to be too costly in that it is not associated (at least for the period of 1 year) with a falloff in the hatching rate, as our results show. Such a strategy observed in other acridids (Greenfield and Pener 1992;Groeters 2006) is particularly well adapted to the Sahelian environment and increases the chance of survival of eggs and will certainly have to be included in the models currently being developed to simulate the population dynamics of the Senegalese grasshopper (Fisker et al 2007;Axelsen 2009). …”
Section: Discussionmentioning
confidence: 98%
“…This 'bet hedging' strategy developed by the Senegalese grasshopper does not seem to be too costly in that it is not associated (at least for the period of 1 year) with a falloff in the hatching rate, as our results show. Such a strategy observed in other acridids (Greenfield and Pener 1992;Groeters 2006) is particularly well adapted to the Sahelian environment and increases the chance of survival of eggs and will certainly have to be included in the models currently being developed to simulate the population dynamics of the Senegalese grasshopper (Fisker et al 2007;Axelsen 2009). …”
Section: Discussionmentioning
confidence: 98%
“…It was made possible for the grasshoppers to delay death by basking in the sun (behavioural fever -a pathogen suppressing strategy described by Blanford et al (1998). It was assumed in the model that grasshoppers, infected but still alive, eat and oviposit normally and that Green Muscle did not harm the alternative prey or other insects in the model (Axelsen 2009). Availability of alternative prey for the birds in the model was simulated to be proportional to the grasshopper density ).…”
Section: The Modelmentioning
confidence: 99%
“…The ecosystem model (Axelsen 2009) simulates the dynamics and migration of O. senegalensis along a five-location, south-north transect running from the southern Sahel to the pastoral zone south of the Sahara desert. The model simulation includes: a natural Sahelian grass in the grassland areas (representing the natural vegetation); millet; natural Sahelian grass as weeds in millet fields prior to manual weeding after 1 month; O. senegalensis; an dipteran egg pod predator Bombyliidae sp., representing all bombyliid species; a coleopteran egg pod predator Tenebrionidae sp., representing all egg pod predatory beetles; the grasshopper Acrotylus blondelii Saussure 1884 as an alternative prey to the egg pod predators; 24 bird species; and an alternative prey for the birds ).…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, each location was split into two compartments, millet fields and grassland, occurring in varying respective proportions. The model has been described in detail by Axelsen (2009) and has also been used to assess the effects of actual treatments from 2003 and 2004 in eastern Niger and to establish how to optimize pesticide treatments (Maiga et al 2009 (Appendix 1), but a small number of parameters had to be found by calibration to available population density data. The data comprised two datasets from Niger and one from Senegal.…”
Section: Introductionmentioning
confidence: 99%